Social networks as an integral and urgent mean of modern teaching at a higher educational establishment - Protsko, Yevheniia (ScienceRise: Pedagogical Education, 2017)
Nowadays it is impossible to find a young person who has nothing to do with the Internet. It has inevitably burst in our lives. The global process of informational technologies development leads to total social networks usage. With different devices (smartphones, PCs, laptops, tablets etc.) young people can check in anytime and anywhere. That’s why to stay in touch with students a teacher has to provide innovative methods and means of teaching. Social networks are good examples of accessibility, moderateness, simplicity in communication and usage. They also provide wide range of opportunities not only to communicate with ease but to study, to be engaged in discussions, investigations, estimations, critical analysis provided by a teacher. According to the newest research Facebook appeared to be one of the most used and popular social network in the world. Recently in Ukraine it is also getting more widespread. The communities formed in the web service help students to incorporate by their interests, skills or even educational subjects, get in touch with the problem raised by a teacher, to discuss it, to solve the given tasks